ZnO@TiO2 heterostructure arrays/carbon cloth by charge redistribution enhances performance in flexible anode for Li ion batteries. (1st February 2019) - Wang, Linlin; Gu, Xianli; Zhao, Lingyu; Wang, Bo; Jia, Chuankun; Xu, Jingli; Zhao, Yufeng; Zhang, Jiujun
Abstract: The intrinsic poor electrical and large volume expansion upon cycling of ZnO raise up challenging kinetic issues. In this work, ZnO@TiO2 core/shell nanorod arrays heterostructure grown directly on carbon cloth is designed and fabricated. The atomic layer deposition coated TiO2 thin layer can not only function as an efficient stress buffer during electrochemical reaction, but also provide enhanced electronic conductivity by forming a heterostructure with ZnO. The ZnO@TiO2 nanorod arrays on carbon cloth can simultaneously achieve the high capacity and high-rate long cycle life (1000 mA h/g for 250 cycles at 1 A/g), which is far superior to that of bare ZnO nanorod arrays on carbon cloth without TiO2 shell. The density functional theory calculations reveal the strong chemical coupling between ZnO and TiO2, which realizes band gap tailoring and significant charge redistribution of both ZnO and TiO2 . Such a unique structure endows the as prepared ZnO@TiO2 on carbon cloth great potential as high performance three-dimensional flexible electrode in Li-ion batteries. Highlights: ZnO@TiO2 arrays heterostructures on carbon cloth were successfully fabricated. The hybrid electrode simultaneously achieves the high capacity and long cycling life. It enhances performance in 3D flexible anode for LIBs by charge redistribution.